Distributed Systems and Big Data Analytics in Predictive Healthcare: Transforming Modern Medicine - Shridhar Bhalekar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The healthcare industry is undergoing a revolutionary transformation driven by the integration of distributed systems and big data analytics. This technological convergence enables real-time decision-making, advanced predictive capabilities, and personalized treatment plans as healthcare data grows exponentially. Traditional processing methods can no longer handle the scale and complexity of data from electronic health records, wearable devices, genomic sequencing, and medical imaging. Distributed computing frameworks like Apache Hadoop, Apache Spark, and cloud-based architectures provide the computational infrastructure to process and analyze this massive data effectively. These technologies enable breakthrough applications in early disease detection, personalized medicine, and operational optimization. Despite promising advancements, significant challenges remain in data integration, security, regulatory compliance, and algorithmic fairness. Emerging trends like edge computing, federated learning, and quantum computing will further expand predictive healthcare capabilities while addressing privacy concerns. The shift from reactive to proactive healthcare delivery promises improved patient outcomes and more efficient resource utilization across the healthcare ecosystem.
Keywords: Distributed Computing; Big Data Analytics; Predictive Healthcare; Personalized Medicine; Healthcare Interoperability